Uitdaging vir volwassene didaktiek: Begeleide selfstudie die oplossing? - H. Klopper (AOSIS, 1995)
The current teaching approach in nursing is mainly tutor-centred: during a formal lecture the tutor provides the facts, the student stays a passive listener and has to memorize facts for reproduction during evaluation. In this paper the argument is focused on a student-centred approach that implies selfstudy with accompaniment when needed. The rationale for this approach is to develop a academic-scientific student, as it is impossible to provide all the information to learners in this technological dispensation. The student is expected to remain a lifelong learner ... "A student cannot claim to have been educated successfully at university or college unless he has learned to study independently".